Implementasi Analisis SWOT dalam Meningkatkan Mutu Pendidikan di Madrasah Tsanawiyah - Amprillah, Bekti (INCARE, International Journal of Educational Resources, 2025)
This study aims to provide deeper understanding of the implementation of SWOT analysis in improving the quality of education in madrasahs. This study also explains: (a) the concept of SWOT analysis, (b) the approach to SWOT analysis, (c) the objectives and benefits of SWOT analysis, (d) the stages of analysis, and (e) the implementation of SWOT analysis at Madrasah Tsanawiyah Al Nahdlah. The method used in this journal is a qualitative research method with a case study approach. Data collection techniques used observation, in-depth interviews, and document analysis. The collected data were then analyzed using SWOT analysis. The SWOT analysis technique used is descriptive qualitative and quantitative analysis using SWOT matrix and SWOT quadrant matrix. The results of this journal conclude that SWOT analysis can be implemented at Madrasah Tsanawiyah Al Nahdlah. Based on the results of the SWOT quadrant matrix analysis, MTs Al Nahdlah is in quadrant 1 (SO strategy) with a total score of strengths greater than the total score of weaknesses and a total score of opportunities greater than the total score of threats.